CLINICAL ASPECTS OF ETHYLMETHYLHYDROXYPYRIDINE SUCCINATE IN ELDERLY PATIENTS WITH CARDIOVASCULAR PATHOLOGY - E. G. Martemianova (Кардиоваскулярная терапия и профилактика, 2018)
Aim. To evaluate efficacy and safety of original ethylmethylhydroxypyridine succinate (Mexidol) in cardiological patients ≥75 year old.Material and methods. In the observational study, according to ethical standards of Khelsinki Declaration, with informed consent, 24 patients participated, age 7588 y. o. Inclusion criteria: age ≥75 y. o.; already diagnosed coronary heart disease (CHD) and/or chronic heart failure (CHF); Mexidol usage. Exclusion criteria: absent informed consent, severe comorbidities. Mean age of the patients at inclusion 80,33±4,06 y. o.; 16 (66,7%) females and 8 (33,3%) males. Patients consequently visited office of cardiologist with the diagnoses: chronic CHD (I25.0I25.9), CHF with preserved systolic function (I50.0I50.9). All patients were consulted by neurologist, had an established diagnosis of cerebrovascular disease (I6567). To reduce the symptoms of frailty, among the neurologist recommendations, with accordance to routine clinical practice, the original Mexidol was included. Mexidol was prescribed by a scheme of manufacturer: intravenous infusions 500 mg x 5 days, then per os 125 mg t. i.d.; overall treatment — 8 weeks.Results. Statistically significant results were noted in 6 months from the study start. There was significant increase of 6 minute walking distance in men from 304,00±87,09 to 388,63±92,28 m (р=0,01), in women from 346,06±56,81 to 427,69±76,87 m (р=0,003); also there were less signs of frailty. No one patient showed significant worsening of the condition; during the overall followup, patients did not call emergency or primary care physicians and did not hospitalize.Conclusion. In comorbidity patients aged ≥75 y. o. at Mexidol treatment, there was increase of 6minute walking test distance, decrease of asthenia signs, that witness for the medication efficacy. All patients showed good tolerability of the drug that witness for safety. Obviously, there are broad trials needed to sum up a gerontological algorithm of CHD and CHF patient management in outpatient setting.